2021
DOI: 10.1002/ps.6667
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the insecticide detoxification carboxylesterase Boest1 from Bradysia odoriphaga Yang et Zhang (Diptera: Sciaridae)

Abstract: BACKGROUND: In insects, carboxylesterases (CarEs) are enzymes involved in the detoxification of insecticides. However, the molecular mechanism of CarE-mediated insecticide metabolism in Bradysia odoriphaga, a serious agricultural pest, remains unclear. The aim of this study is to investigate the detoxification process of malathion, bifenthrin, and imidacloprid by B. odoriphaga carboxylesterase (Boest1).RESULTS: An alpha class CarE gene Boest1 was cloned from B. odoriphaga. The results of real-time quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 59 publications
(141 reference statements)
0
11
0
Order By: Relevance
“…These results agreed with a previous study in which Boest1, an α esterase of B. odoriphaga, was most highly expressed in the midgut, suggesting that the midgut plays a key role in metabolizing toxic xenobiotics. 22 Similarly, SlCOE030 was also found to be induced by ricin, imidacloprid, xanthotoxin, and fluralaner. 23,48 We believed that SlCOE030 is a particular detoxification gene of α-esterase, which may be induced simultaneously by plant compounds or synthetic insecticides due to the coevolution between S. litura and tobacco.…”
Section: ■ Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…These results agreed with a previous study in which Boest1, an α esterase of B. odoriphaga, was most highly expressed in the midgut, suggesting that the midgut plays a key role in metabolizing toxic xenobiotics. 22 Similarly, SlCOE030 was also found to be induced by ricin, imidacloprid, xanthotoxin, and fluralaner. 23,48 We believed that SlCOE030 is a particular detoxification gene of α-esterase, which may be induced simultaneously by plant compounds or synthetic insecticides due to the coevolution between S. litura and tobacco.…”
Section: ■ Discussionmentioning
confidence: 92%
“…For example, the decomposition rates of malathion and bifenthrin after incubation with the recombinant Boest1 protein of B. odoriphaga were 27.14 and 31.42%, respectively. 22 The CarE6 protein of T. cinnabarinus decomposed 41.7% of fenpropathrin, indicating that the CarE6 protein effectively metabolized fenpropathrin. 20 In the present study, the specific activities of the in vitro expressed SlCOE030 protein toward α-NA and β-NA were determined, and the results indicated that the recombinant protein was sufficient to test the capacity of the SlCOE030 protein to metabolize cyantraniliprole (Table 2).…”
Section: ■ Discussionmentioning
confidence: 97%
See 3 more Smart Citations